Differential Gene Expression Profile of Human Neutrophils Cultured with Plasmodium falciparum-Parasitized Erythrocytes. (5th July 2018) - Terkawi, Mohamad Alaa; Takano, Ryo; Kato, Kentaro
Abstract : Neutrophils (PMNs) are the most abundant cellular component of our innate immune system, where they play central roles in the pathogenesis of and resistance to a broad range of diseases. However, their roles in malarial infection remain poorly understood. Therefore, we examined the transcriptional gene profile of human PMNs in response to Plasmodium falciparum -parasitized erythrocytes (iRBCs) by using oligonucleotide microarrays. Results revealed that PMNs induced a broad and vigorous set of changes in gene expression in response to malarial parasites, represented by 118 upregulated and 216 downregulated genes. The transcriptional response was characterized by the upregulation of numerous genes encoding multiple surface receptors, proteins involved in signal transduction pathways, and defense response proteins. This response included a number of genes which are known to be involved in the pathogenesis of malaria and other inflammatory diseases. Gene enrichment analysis suggested that the biological pathways involved in the PMN responses to the iRBCs included insulin receptor, Jak-STAT signaling pathway, mitogen-activated protein kinase (MAPK), and interleukin and interferon-gamma (IFN- γ ) signaling pathways. The current study provides fundamental knowledge on the molecular responses of neutrophils to malarial parasites, which may aid in the discovery of novel therapeutic interventions.